SUSTAINABLE DEVELOPMENT GOALS TO STRENGTHEN INDONESIAN PALM OIL DEVELOPMENT THROUGH INDONESIAN SUSTAINABLE PALM OIL (ISPO) - Ermanto Fahamsyah; Brigitta Amalia Rama Wulandari; Yusuf Adiwibowo (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2021)
The palm oil development provides many advantages for Indonesia. One of which is that the development of Indonesian palm oil came fast and contributed a lot to the country's economic sectors. There are also other organic oil-based, such as jatropha, camelina, soybean and rapeseed. However, compared the palm oil to the other base of the organic oil materials, palm oil price outperforms the others oil-based because of the stability of the palm oil price. Palm oil benefits the Indonesian economy and the triple bottom line of John Elkington: people, planet, and profit. However, there is a critical issue with palm oil production. Its production is believed not to apply sustainability principles. Thus, it can damage and ruin the natural environment in Indonesia; for example, it damaged the area where the Sumatran tiger, Sumatran Orang Utan, and Borneo Orang Utan lived. Through the ministry of agriculture, the government established Indonesian Sustainable Palm Oil (ISPO) to answer this critical issue and recover the sustainability aspect of Indonesian palm oil. Abstrak: Indonesia beruntung karena dapat menikmati berbagai manfaat dari pembangunan kelapa sawit yang merupakan salah satu ciri dan keuntungan tersendiri yang Indonesia miliki, pembangunan kelapa sawit Indonesia sangat cepat dan pesat serta memberikan kontribusi yang tinggi terhadap negara melalui sektor ekonomi, jika dibandingkan dengan minyak nabati lainnya seperti : jathropa, camelina, soy bean dan rapeseed, kelapa sawit lebih unggul dari segi ekonomi yang mana dari segi harga lebih stabil jika dibandingkan minyak nabati dengan bahan baku lainnya. Minyak kelapa sawit memberikan berbagai manfaat bagi Indonesia selain daripada ekonomi juga terhadap triple bottom line sebagaimana dikemukakan oleh John Elkongton yakni people, planet dan profit sehingga dalam pemanfaatannya memberikan dampak yang baik meski begitu tetap saja dihadapkan dengan berbagai critical issue mengenai kelapa sawit. Dalam kegiatan produksi kelapa sawit diyakini bahwa belum mengedepankan aspek keberlanjutan yang kemudian berdampak terhadap kerusakan lingkungan di Indonesia. Kata Kunci: Indonesia, ISPO, Pembangunan Kelapa Sawit, Aspek Keberlanjutan, Triple Bottom Line